Potential therapies for immune-related adverse events associated with immune checkpoint inhibition: from monoclonal antibodies to kinase inhibition - Meagan‐Helen Henderson Berg; Sonia V. del Rincón; Wilson H. Miller (2022)
The therapeutic benefits of immune checkpoint inhibitors (ICIs), which enable antitumor immune responses, can be tempered by unwanted immune-related adverse events (irAEs). Treatment recommendations stratified by irAE phenotype and immunohistopathological findings have only recently been proposed and are often based on those used in primary autoimmune diseases, including targeting of specific proinflammatory cytokines with monoclonal antibodies. Increasing evidence supports the use of such antibody-based strategies as effective steroid-sparing treatments, although the therapies themselves may be associated with additional drug toxicities and reduced ICI efficacy. Kinases are key contributors to the adaptive and innate responses that drive primary autoimmune diseases and irAEs. The janus kinase/signal transducer and activator of transcription, Bruton’s tyrosine kinase, and mitogen-activated protein kinase-interacting serine/threonine protein kinases 1 and 2 pathways are also critical to tumor progression and have important roles in cells of the tumor microenvironment. Herein, we review the histopathological, biological, and clinical evidence to support specific monoclonal antibodies and kinase inhibition as management strategies for irAEs.